2017
DOI: 10.1093/jxb/erx249
|View full text |Cite|
|
Sign up to set email alerts
|

Crop-model assisted phenomics and genome-wide association study for climate adaptation of indica rice. 1. Phenology

Abstract: Phenology and time of flowering are crucial determinants of rice adaptation to climate variation. A previous study characterized flowering responses of 203 diverse indica rices (the ORYTAGE panel) to ten environments in Senegal (six sowing dates) and Madagascar (two years and two altitudes) under irrigation in the field. This study used the physiological phenology model RIDEV V2 to heuristically estimate component traits of flowering such as cardinal temperatures (base temperature (Tbase) and optimum temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Similar results have been recently reported for flowering time as a complex trait (Dingkuhn et al 2017a). Despite this advantage of model-based dissection analysis over complex traits like grain yield per se, the latter approach cannot be replaced completely.…”
Section: Crop Modelling Helps To Elucidate the Genetic Control Of Grasupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results have been recently reported for flowering time as a complex trait (Dingkuhn et al 2017a). Despite this advantage of model-based dissection analysis over complex traits like grain yield per se, the latter approach cannot be replaced completely.…”
Section: Crop Modelling Helps To Elucidate the Genetic Control Of Grasupporting
confidence: 85%
“…Mangin et al (2017) showed that crop models can be used to develop "stress indicators" that explain yield variation across multiple environments, facilitating GWAS application to identify relevant QTLs for yield in response to environmental stresses. Similarly, Dingkuhn et al (2017a) and Dingkuhn et al (2017b) have shown that the crop model RIDEV can dissect phenology and spikelet sterility, respectively, into their components, thereby heuristically strengthening the phenotyping and GWAS analysis of these two traits. These studies demonstrated benefit of crop modelling in GWAS analysis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The explicit representation of key ecophysiological processes is thus crucial to allow the model to properly interpret the complex genotype ´ environment ´ management interactions characterizing the underlying system. Moreover, the direct relationships between model parameters and plant tolerance traits make this model suitable for decomposing complex traits ("salt tolerance") into simple ones, in turn allowing the exploration of associations between traits and molecular markers (Dingkuhn et al, 2017). As an example, the parameter "threshold leaf sodium concentration" could relate to candidate genes NHX and AVP involved with the sequestration of Na + into leaf vacuoles (Munns and Tester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Potato disease modelling, foresight, further model development Kroschel et al, 2013 [167]; Sporleder et al, 2013 [168]; Condori et al, 2014 [169]; Carli et al, 2014 [170]; Kleinwechter et al, 2016 [171]; Kroschel et al, 2017 [172]; Fleisher et al, 2017 [173]; Raymundo et al, 2017 [174]; Raymundo et al, 2017 [175]; Quiroz et al, 2017 [176]; Ramirez et al, 2017 [177]; Mujica et al, 2017 [178]; Scott and Kleinwechter, 2017 [179]; Petsakos et al, 2018 [180] AfricaRice: Model improvement, yield gap analysis, genotype × environment interactions, impact of climate change van Oort et al, 2014 [181]; van Oort et al, 2015 [182]; van Oort et al, 2015 [183]; Dingkuhn et al, 2015 [184]; van Oort et al, 2016 [185]; El-Namaky and van Oort, 2017 [186]; van Oort et al, 2017 [187]; Dingkuhn et al, 2017 [104,105]; van Oort and Zwart, 2018 [188]; van Oort, 2018 [189], Duku et al, 2018 [190] ICRAF: Agroforestry and intercropping modelling Africa Luedeling et al, 2014 [191]; Araya et al, 2015 [192]; Luedeling et al, 2016 [193]; Smethurst et al, 2017 [194], Masikati et al, 2017 [195] ILRI: crop-livestock-farm interactions Van Wijk et al, 2014 [196]; Herrero et al, 2014 [197] IITA: Modelling on Yams in West Africa Marcos et al, 2011 [198]; Cornet et al, 2015 [199]; Cornet et al, 2016 [200] ICARDA: Climate variability and change impact studies, foresight, conservation agriculture impact, genotype × environment interactions Sommer et al, 2013 [201]; Bobojonov and Aw-Hassan, 2014…”
Section: Cipmentioning
confidence: 99%